Cooperative Learning Method Integrated Cartoon Picture Pinterest Media on Student’s Descriptive Writing Ability at SMP Negeri 1 Siantar - Indah Dame Nababan; Dumaris E Silalahi; Irene Adryani Nababan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
English plays a vital role as a global language and an essential skill for academic and professional success. Among the four language skills, writing is the most challenging for Indonesian EFL learners, particularly in descriptive text production, due to limited vocabulary, grammatical difficulties, and lack of exposure to authentic English use. Traditional teaching methods often fail to provide adequate engagement and creativity, resulting in students’ low writing performance. To address these issues, this study investigated the effect of applying the Cooperative Learning method of the learning together model integrated with cartoon picture media from Pinterest on students’ descriptive writing ability at SMP Negeri 1 Siantar. The research employed a quantitative approach with a quasi-experimental design. The population consisted of 237 eighth-grade students, from which class VIII-4 was selected as the experimental group and class VIII-5 as the control group. Data were collected through pre-tests and post-tests, and analyzed using mean, standard deviation, normality, homogeneity, and independent sample t-test. The results revealed a significant improvement in the experimental class, with the mean post-test score increasing from 39 to 80, compared to the control class which only rose from 46 to 59.2. The t-test result (7.722) exceeded the t-table value (1.677) at the 0.05 significance level, confirming that the treatment had a positive effect. It can be concluded that the integration of Cooperative Learning with cartoon picture media from Pinterest is effective in enhancing students’ descriptive writing ability. This method not only improved writing scores but also fostered greater motivation and active participation in the classroom.